EVOLUTION OF STABLE CARBON ISOTOPE COMPOSITIONS FOR METHANE AND CARBON DIOXIDE IN FRESHWATER WETLANDS AND OTHER ANAEROBIC ENVIRONMENTS - Hornibrook E.R.C.; Longstaffe F.J.; Fyfe W.S. (My University, 2000)
Two types of distribution for αC values are observed in anaerobic environments when δ13C–ΣCO2 and δ13C–CH4 values are measured across gradients of depth or age of organic debris. The type-I distribution involves a systematic increase in αC values with depth as a result of decreasing δ13C–CH4 and increasing δ13C–ΣCO2 values. This behavior corresponds to a progressive increase in the prevalence of methanogenesis by the CO2 reduction pathway relative to acetate fermentation. Utilization of autotrophically formed acetate by methanogens would also cause an increase in αC values. The type-II distribution occurs when both δ13C–CH4 and δ13C–ΣCO2 values decrease with depth, resulting in approximately constant αC values. This condition corresponds with a strong dependence of methanogens on porewater ΣCO2 as a carbon source by way of either the CO2 reduction pathway or utilization of autotrophically formed acetate.